Enhancing Administrative Efficiency Through Archive Management at the Malalayang District Office, Manado City, Indonesia - Mandulangi, Jufrina; Mundung, Deky Eko Wibowo; Makinggung, Juliet Pauladel Truly; Tuwaidan, Altje Ellen (International Journal of Business and Applied Economics, 2024)
Archives serve as the institutional memory, supporting administrative processes and ensuring efficient operations. However, initial observations at the Malalayang District Office revealed significant deficiencies in archive management. These included a lack of standardized procedures, inadequate retrieval methods, and insufficient facilities. To address these issues, this research aims to investigate the strategies implemented, challenges faced, and solutions adopted to improve archive management and streamline administrative processes at the Malalayang District Office. Employing a qualitative case study methodology, data were collected and analyzed through a systematic process of reduction, presentation, and conclusion drawing, followed by verification. The findings of this research offer valuable insights into effective archive management practices and their contribution to enhancing administrative efficiency.